Azadirachta indica A. Juss. (NEEM) : Reproductive Studies in Relation to Growth Regulator Treatments - Sabherwal, Suhani; Dhir, K. K. (Indian Forester, 2012)
The in vivo morpho-physiological responses to kinetin-GA3 and kinetin-spermidine combination treatments in Neem (Azadirachta indica) were studied during annual reproductive flushes from bud development onwards to seed set. The buds and flowers per inflorescence were higher in kinetin-spermidine treated branches than kinetin-GA3. Protein, total sugars and reducing sugars measured higher following 0.5 mM kinetin/0.2 mM spermidine treatments as compared to 0.5 mM kinetin/0.5 mM spermidine. 0.5 mM kinetin/0.5 mM GA3 treatments produced poor flowering response, longer juvenility and low contents of the above biochemical analyses than 0.5 mM/0.2 mM GA3. The enzyme assay of invertase, protease, acid- and alkaline phosphatases matched the biochemical responses to the growth regulator treatments. In control, a shorter regeneration phase leads to lower productivity of floral inflorescence and fruit set. Therefore, it is suggested that the application of kinetin-spermidine combination treatment may regulate the reproductive phase resulting in improved morpho-physiological characteristics.